Methods of Selection and Maintenance of Experimental Animals for Biomedical Research - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
A B S T R A C TResearch is an activity carried out based on scientific principles and methodssystematically to obtain information, data, and information from relatedsubjects, with understanding the theory and proving assumptions and / orhypotheses. The results obtained are conclusions that can be applied orbecome additional knowledge for the progress of science. However, researchactivities must still respect the rights and dignity of research subjects.Health research includes biomedical, epidemiological, social, and behavioralresearch. Some health research can be done in vitro, using mathematicalmodels, or computer simulations. If the research results are to be used forhumans, further research is needed using living materials (in vivo) such ascell lines and tissue cultures. However, to observe, study, and conclude alloccurrences in living things as a whole, experimental animals are neededbecause experimental animals have a value for each part of the body andthere are interactions between these body parts.